Influence of fiber reinforcement towards the physical characteristics of low density polyethylene laminated composites - Ravichandran, S.; Raj, A. Daniel; Visvanath, P. Balaji; Mohammad, Faruq; Al-Lohedan, Hamad A.; Sagadevan, Suresh (Polimery, 2020)
In recent years, the increased interest in the design and fabrication of lightweight polymer composites with various combinations and stoichiometry is due to their enhancement of electrical, mechanical, thermal, and biological properties compared to the properties of conventional materials. With that view, the present study deals with the effects of low density polyethylene composites (LDPE) reinforced with epoxy resin, glass fiber, carbon fiber, and Kevlar towards the mechanical, thermal, and water absorption properties. The mechanical studies showed that the LDPE composite reinforced carbon fiber has the best tensile properties compared to other composites and this can be mostly due to the proper bonding and associated interaction between the polymeric matrix and the bidirectional layer of the fibers. Also, the carbon fiber reinforced composite has superior properties of impart energy compared to the other composites and the non-reinforced ones and this is attributed to the crystalline nature of carbon fiber. Further studies of the thermal properties indicated that the retention of thermal stability for all the fiber-reinforced polymer composites, while the water absorption revealed a considerable increase in the weight of Kevlar fiber-reinforced composite. From the overall analysis, the enhanced properties of LDPE matrix reinforced fibers are linked to the morphological changes that occurred and are directly affected by the nature of the fiber.